Tendências de moda e posicionamento de marca (ModaPalavra e-periódico, 2014)
Innovation is a constant challenge to brands today. Searching for innovation opportunities, brands invest money and time. Facing the frequent market changes, especially in the fashion market, it is a challenge to companies to maintain a strong position. This paper aims to evaluate the level of trend’s adoption by the brand Ellus 2ndFloor, already consolidated in the Brazilian market. It was intended to assess the volatility of a fashion brand’s positioning facing the imperative renovation of trends.
Keywords: trends; brand; positioning